Contact-Free Mortuary Trolley Design as a Device for the Mobility of Covid-19 Victims - Vania Katherine Mulia; Nanda Indriana; Qurriyatus Zahro; Farid Triawan (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2021)
The Covid-19 pandemic has caused many issues, especially in the medical field. One of the groups that are affected by the pandemic the worst is the health workers. The surge of demand for health services, especially for Covid-19 patients, overwhelms health workers, forcing them to work extra hard and eventually experience exhaustion. Due to this condition, the health workers may face difficulties in doing heavy-duty work. This paper proposes a design of a mortuary trolley as a device to ease the health workers in handling the dead bodies of Covid-19 victims. Considering the need for a corpse mobility aid that is contact-free, the design utilizes a combination of a scissor lift structure, a power screw mechanism to elevate and lower the table, and a conveyor system to load and unload the table. To ensure that the device can operate without experiencing unwanted failure, strength analyses are done on the most critical components, such as the scissor arm, pin joint, power screw, and scissor arm connector, to determine the safety factor at maximum load in static and fatigue loading condition. Analysis results show that all those components have a safety factor greater than 1 for both static and fatigue loading conditions, indicating the device will not yield and is predicted to have infinite life. The design and analyses of this device can be a reference for manufacturers of medical devices to design a mortuary trolley to ease the work of health workers.